2016
DOI: 10.7710/2162-3309.1204
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating an Open Access Publishing Fund at a Comprehensive University

Abstract: INTRODUCTION As the open access movement has fostered a shift from subscriber-funded journals to author-pays models, scholars seek funding for the dissemination of their research. In response to this need, some libraries have established open access funds at their institutions. This paper presents an evaluation of an open access fund at a comprehensive university. DESCRIPTION OF PROGRAM/SERVICE Wanting to learn how faculty have benefitted from an open access publishing fund, Grand Valley State University Libra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 16 publications
1
6
0
Order By: Relevance
“…Clearly, some high-impact research is being funded with library OA funds, despite two common fund restrictions that could limit impact: The "last resort" requirement makes it less likely that a grant-funded project would be funded (on the assumption that grantfunded projects have a higher likelihood of being high-impact research), and the nearuniversal limit of hybrid publication funding mostly eliminates the ability to fund articles for publication in many of the highest-impact subscription model journals. These high-impact publications confirm that faculty's self-reported interest in OA publishing to increase their visibility discussed earlier is legitimate, and can result in not only a high citation count but also in a high Altmetric Attention Score (Beaubien et al, 2016;Teplitzky & Phillips, 2016).…”
Section: Impactsupporting
confidence: 69%
See 1 more Smart Citation
“…Clearly, some high-impact research is being funded with library OA funds, despite two common fund restrictions that could limit impact: The "last resort" requirement makes it less likely that a grant-funded project would be funded (on the assumption that grantfunded projects have a higher likelihood of being high-impact research), and the nearuniversal limit of hybrid publication funding mostly eliminates the ability to fund articles for publication in many of the highest-impact subscription model journals. These high-impact publications confirm that faculty's self-reported interest in OA publishing to increase their visibility discussed earlier is legitimate, and can result in not only a high citation count but also in a high Altmetric Attention Score (Beaubien et al, 2016;Teplitzky & Phillips, 2016).…”
Section: Impactsupporting
confidence: 69%
“…Most faculty indicated that they chose to publish OA in order to increase the visibility of their work. Many expressed support for the OA movement, and noted that they would not have been able to pay the APC without the library OA fund (Beaubien, Garrison, & Way, 2016). University of California Berkeley librarians also surveyed the 138 recipients of APC funding from the Berkeley Research Impact Initiative (BRII).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Lately the main commercial and society publishers have gradually started new OA outlets (Peters, 2013) and have reorganised several subscription journals into APC-financed models. Journals that embraced the autonomous scholar-published OA journal model anticipative are hardly ever contingent on APC-funding, which may be a hindrance for some potential contributors without resources or mechanisms to pay for their articles (Beaubien, Garrison, & Way, 2016). Despite the fact that OA literature is accessible without restriction to readers, there are nevertheless expenses related to producing or publishing OA material.…”
Section: Peer Review: History and Futurementioning
confidence: 99%
“…Even though some contributors use grant funds to cover the fees, there is still a substantial percentage of authors who either cannot get grant funding or the resources to pay for them on their own. The paucity of available funds generates an obstruction to both the author's career, which is conditional on publication and circulation, in addition to the shift of academic publishing to an OA model (Beaubien, Garrison, & Way, 2016).…”
Section: Peer Review: History and Futurementioning
confidence: 99%
“…It also outlined several libraries' decisions resulting from reconsideration of their OA funds, primarily initiated due to financial constraints. Qualitative assessment was undertaken by Beaubien, Garrison, and Way (2016). They surveyed authors who had received grants from their library's OA fund, to assess whether the fund was meeting its intended purposes.…”
Section: Literature Reviewmentioning
confidence: 99%